2013
DOI: 10.1002/pmic.201200444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Annexin A1 interacting proteins in chronic myeloid leukemia KCL22 cells

Abstract: In the present study, we used a functional proteomic approach to identify Annexin A1 (Anxa1) interacting proteins in the Philadelphia-positive KCL22 cell line. We focused on Anxa1 because it is one of the major proteins upregulated in imatinib-sensitive KCL22S cells versus imatinib-resistant KCL22R. Our proteomic strategy revealed 21 interactors. Bioinformatic analysis showed that most of these proteins are involved in cell death processes. Among the proteins identified, we studied the interaction of Anxa1 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, some reports have suggested that JAK activation is dependent on BCR-ABL, whereas others did not (Carlesso et al, 1996;Colavita et al, 2013;Hoelbl et al, 2010;Nair et al, 2012b;Coppo et al, 2006). Furthermore, it was reported that JAK inhibitors were only effective against CML when BCR-ABL was inhibited by nilotinib (Coppo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some reports have suggested that JAK activation is dependent on BCR-ABL, whereas others did not (Carlesso et al, 1996;Colavita et al, 2013;Hoelbl et al, 2010;Nair et al, 2012b;Coppo et al, 2006). Furthermore, it was reported that JAK inhibitors were only effective against CML when BCR-ABL was inhibited by nilotinib (Coppo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we hypothesize that the survival of LSCs might not be affected by the inhibition of BCR-ABL kinase activity during IMA treatment. Therefore, it might be necessary to inhibit other signaling pathways in addition to BCR-ABL kinase activity (Corbin et al, 2011;Colavita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately,t he BCR-ABL1-independent mechanisms of resistance in CML have been poorly characterized. [28][29][30][31] Finally the activity of ac ompound against ac ell line does not depend only on the isolated activity against an enzymet arget but also depends on cellular permeation, cellular compartment localization,s tability of the compound in cells and promiscuity of compound toward binding to other cellular proteins (both kinase and non-kinase targets). Ac ompound that potently inhibits ABL1 but also binds to other cellular macromolecules and/or localizes into compartments that BCR-ABL1 does not reside will not display the same potencya gainst the target protein as was seen in an in vitro assay.C ompounds 16 (HSN608)a nd 15 (HSN459)a re of interestb ecause in addition to potent activity againstd rug-resistant CML cell line, KCL22-IR, they have lower logP values (2.3 and 2.7, respectively)t han the rest of the active compounds and therefore are more drug-like in comparison.…”
Section: Aminoisoquinolinesand Aminonaphthyridines Potently Inhibit Tmentioning
confidence: 99%
“…However, resistance to TKI is a vital aspect of Ph + ALL due to the emergence of breakpoint cluster region (BCR)-Abelson murine leukemia viral oncogene homolog 1 (ABL) mutations (25). Previous studies have suggested that upon TKI treatment pressure, chronic myelogenous leukemia (CML) stem cells survive due to BCR-ABL kinase-independent mechanisms (69). …”
Section: Introductionmentioning
confidence: 99%